What drives travellers adoption of online travel reviews? integrating helpfulness with information adoption factors - Islam, Md. Tariqul; Hussin, Siti Rahayu; Wong, Foong Yee (Taylor's University, 2023)
Online travel reviews are shared by individuals who have experienced and consumed tourism products and services. Consumers perceptions, evaluations, and experiences towards any product or service are highlighted in online reviews. This study investigates the factors that drive travellers adoption of online travel reviews using a quantitative, survey-based, and cross-sectional approach. A total of 223 respondents participated in the current study. SPSS (v.26) and SmartPLS (v.3.3.9) software were employed to conduct the data analyses. The studys findings indicate that review quality, reviewer credibility, review usefulness, and review helpfulness influence travellers adoption of online reviews. In addition, the current study provides both theoretical and practical implications. Theoretically, a novel theoretical model was developed by integrating information helpfulness with the Information Adoption Model (IAM) factors to identify the determinants of online travel reviews. Practically, the findings provide several implications for tourism consumers and marketers. Finally, the paper concludes by highlighting its limitations and suggesting directions for future studies.